Multifocal intraocular lens technology: biomaterial, optical design and review of clinical outcomes. (August 2011) - Packer, Mark
Presbyopia is the age-related loss of accommodative function with age and the reason that almost all people need reading glasses, bifocals or some other optical correction after the age of 45 years. Presbyopia-correcting intraocular lens implants (IOLs) have been developed to overcome the need for eyeglasses or contact lenses for high-resolution near vision (i.e., reading) in adulthood. These presbyopia-correcting IOLs and can be classified as either accommodative or multifocal. Accommodative presbyopia-correcting IOLs are designed to change optical power by changing position, shape or index of refraction with accommodative effort. These IOL designs have demonstrated a range of accommodative potential. Multifocal IOLs correct presbyopia by focusing incoming light at two or more focal points; they can be further classified as refractive or diffractive. A Cochrane systematic review concluded that multifocal IOLs were effective at improving near vision when compared with monofocal IOLs and that unaided distance visual acuity was similar in the two groups. Unwanted optical side effects of multifocal IOLs, however, may include reduced contrast sensitivity, halos around point sources of light and glare. Whether the benefits of improvement in near unaided acuity outweigh the optical side effects of multifocal IOLs will vary among patients, with important factors being the motivation to achieve spectacle independence and adaptation over time. Multifocal IOLs may produce a symptomatic reduction in the quality of distance, intermediate or near vision, particularly if other ocular pathology is present, such as ocular surface disease, corneal dystrophy, zonulopathy, macular disease or impairment of the pathways from the optic nerve to the visual cortex. Therefore, the candidacy of patients with amblyopia or abnormalities of the cornea, macula or optic disc must be considered carefully. Along with preoperative and postoperative counseling, accurate biometry and meticulous surgical technique, differences in material, structure and optical design of multifocal IOLs influence the resulting success in terms of patient satisfaction and clinical outcomes. This article seeks to differentiate currently available multifocal IOL technologies on the basis of 15 years of personal experience, peer-reviewed publications and US FDA clinical investigations to aid clinicians in their daily endeavor to provide greater quality of vision and enhanced quality of life for their patients.